Dissociation of visual extinction and neglect in the left hemisphere. (August 2020) - Beume, Lena-Alexandra; Rijntjes, Michel; Dressing, Andrea; Kaller, Christoph P.; Hieber, Maren; Martin, Markus; Kirsch, Simon; Kümmerer, Dorothee; Urbach, Horst; Umarova, Roza M.; Weiller, Cornelius
Abstract: Visual neglect and extinction are two distinct visuospatial attention deficits that frequently occur after right hemisphere cerebral stroke. However, their different lesion profiles remain a matter of debate. In the left hemisphere, a domain-general dual-loop model with distinct computational abilities onto which several cognitive functions may project, has been proposed: a dorsal stream for sensori-motor mapping in time and space and a ventral stream for comprehension and representation of concepts. We wondered whether such a distinction may apply to visual extinction and neglect in left hemisphere lesions. Of 165 prospectively studied patients with acute left hemispheric ischemic stroke with a single lesion on MRI, 122 had no visuospatial attention deficit, 10 had extinction, 31 neglect and 2 had both, visual extinction and neglect. Voxel-based-lesion-symptom mapping (VLSM, FDR<.05) showed a clear anatomical dissociation. Extinction occurred after damage to the parietal cortex (anterior bank of the intraparietal sulcus, inferior parietal lobe, and supramarginal gyrus), while visual neglect occurred after damage mainly to the temporal lobe (superior and middle temporal lobe, anterior temporal pole), inferior ventral premotor cortex, frontal operculum, angular gyrus, and insula. Direct comparison of both conditions linked extinction to intraparietal sulcus and supramarginal gyrus (FDR<.05). Thus, in the left hemisphere extinction seems to be related to dorsal stream lesions, whereas neglect maps more on the ventral stream. These data cannot be generalized to the right hemisphere. However, a domain-general point-of-view may stimulate discussion on visuospatial attention processing also in the right hemisphere.